From Neglect to Opportunity: Revitalizing a neglected coastline through adaptive reuse architecture that unites and celebrates - Herbert, Rachel (School of Architecture, Planning and Geomatics, 2024)
This dissertation explore s the notion and larger benefits of adaptive reuse architecture in becoming a catalyst for revitalisation and integration , through bringing public activity to an underutilised portion of coastline . By designing with the principles of purpose and connection, architects can create spaces that embrace the natural elements and factors such as the inevitability of weathering. This thesis explore s conscious design methods associated derived from adaptive reuse principles ; innovative waste management and preserving significant features associated with the existing, enhancing the site's cultural and social connections to related communities . The project centre s around the present day and future transformation s of a dilapidated Crayfish Factory and it's unknown landscape , into a thriving coastal edge of opportunity. The intention of the project is to promote adaptive reuse as a means of revitalising and unifying both structure and context in the eyes of the surrounding communities. This thesis aims to unpack the challenges and opportunities that arise when working with rugged conditions, existing structures and complex neighbourhood interrelations. The greater intention of this work is to expand upon adaptive reuse as an architectural methodology. For it to not only be seen as a means to promoting sustainable construction within the built environment but also to capitalise on the opportunity of enhancing the existing fabric and spatial relations by embracing the character of the existing with personalised intervention that merges past, present and future use. On a technical level this is understood by observing both natural weathering and designed material degradation to explore means of architecture embracing its own evolution . This is done in the pursuit of creating ‘ whole' architecture . Fabricating divers e spaces and functionings to excite the everyday, all the while planting the seed of versatility for the future, allowing the structure to grow and adapt with each new generation of use. The common theme of conscious design is achieved by maintaining the narrative that buildings should not be considered as isolated objects, but rather as malleable components within a larger constantly evolving ecosystem. With this in mind, the intention of the project can also be seen in its material nature; promoting both environmental and social integration.